MANAGEMENT OF INFRASTRUCTURE FACILITIES IN IMPROVING THE QUALITY OF EDUCATION IN SDN DESA SUNGAI PANTAI, RANTAU BADAUH SUB-DISTRICT, BARITO KUALA DISTRICT - Winarti Winarti; Husnul Madihah; Jarkawi Jarkawi (Penerbit Lafadz Jaya, 2023)
This study aims to analyze the management of infrastructure facilities in improving the quality of education at SDN Desa Sungai Pantai, Rantau Badauh Sub-district, Barito Kuala Regency. This study used a qualitative approach with interview, observation and documentation methods to collect data from principals, teachers, school guards, school committees and student guardians from three different primary schools in Sungai Pantai village. Based on interviews with relevant parties at the three primary schools in Sungai Pantai village, it can be concluded that infrastructure management plays a very important role in improving the quality of education. Adequate infrastructure, such as comfortable classrooms, complete libraries, science laboratories and adequate sports areas, provide opportunities for students to learn and develop to their full potential. In addition, good infrastructure management involves regular maintenance and care of school facilities. Government and community support is also very important in maintaining the condition of infrastructure facilities and meeting the required standards. Cooperation between the government, school and community is needed to ensure optimal infrastructure conditions. The results also show that good infrastructure management has a positive impact on the learning process. Students can learn comfortably and optimally, teachers can teach effectively, and learning activities can be interactive and diverse.